(untitled) (Baghdad Science Journal, 2025)
During recent years, there has been an increasing interest in the investigation of the cytokines roles in pathogenesis of cancer, thus the study aimed at evaluating the level of tumor necrosis factor-alpha(TNF-?) in sera of Iraqi multiple myeloma (MM) patients. Beta 2-microglobulion (?2-m) was assessed to determine if there was any association between this cytokine and the level of ?2- m, as the latter is related to the stage of the disease. In addition, the age and gender were also taken into consideration. Furthermore, we investigated the relationship between IgG and TNF-? in sera of patients. 49 Iraqi patients (27 males and 22 females).The patients were also divided into two groups: the first group included (17) patients who were recently diagnosed and not received any treatment at the time of collecting samples while the second group included (32) patients who received treatment. A further group was also investigated which included (12) apparently healthy individuals (9 males and 3 females), who were regarded as a control group. Serum TNF-? and ?2- m were determined using enzyme-linked immunosorbent assay (ELISA).while the concentration of IgG was measured by radial immune diffusion plates The study reached to the following results: TNF-? levels were not significantly elevated in the patients with MM compared to control group (5.98 ± 8.47 SD vs. 4.85 ± 12.1 SD) and no significant differences (P > 0.05) were observed in the mean (6.02 ±8.1SD vs 5.9 ±9.4SD) concentration of TNF-? in patients with MM who received treatment, when compared with those who did not take the treatment .In addition, there are positive significant correlations between TNF-? and ? 2 Microglobulin (r = 0.316, P = 0 .027), and no relationship between IgG and TNF-? (r = - 0.032, P = 0.829).Furthermore, the study observed that, there was no correlation between TNF-? on the one hand and factors of age and gender on the other hand.